Incidence and risk factors of severe acute high-altitude illness in healthy adults first entering the northern Tibetan Plateau of over 5,000 m - Gao, Chun; Qi, Guo-Dong; Wang, Dan; Zhang, Zhao-Hui; Liu, Zhong-Xing; Ge, Rui-Dong; Yong, Zong; Yan, Li-E (Frontiers in Public Health, 2024)
Background Our study was designed to determine the incidence and risk factors of severe acute high-altitude illness (AHAI) in healthy adults first entering the northern Tibetan Plateau of over 5,000 m. Methods In our prospective observational study, we enrolled 500 people who were scheduled for fast ascension to the northern Tibetan Plateau. The primary outcome variable was severe AHAI, defined as the presence of serious symptoms that could not be ameliorated by general treatment and required evacuation to lower altitudes. According to the inclusion and exclusion criteria, a cohort of 383 healthy people was included in the statistical analysis. We calculated the incidence of severe AHAI, identified the risk factors, and the differences in the most severe symptoms experienced. Results Sixty-eight people were diagnosed with severe AHAI, and the incidence was 17.8%. Compared to individuals without severe AHAI, those with severe AHAI were more likely to be over the age of 40 years, of Han Chinese nationality, and living at an altitude of <1,500 m. They were less likely to belong to the Yi nationality, had a lower altitude of permanent residence, and exhibited decreased levels of lymphocyte count and hemoglobin concentration. Multivariable logistic regression showed that the mean altitude of permanent residence [per kilometer, adjusted odds ratio (AOR) = 0.464; 95% confidence interval (CI), 0.304–0.708; p < 0.001] and lymphocyte count (AOR = 0.606; 95% CI, 0.378–0.970; p = 0.037) were the independent risk factors. Headache and dyspnea ranked in the top two of the most severe symptoms for people with severe AHAI. Conclusion Living at lower altitudes and having a decreased lymphocyte level were the risk factors of severe AHAI in healthy adults first entering the plateau of over 5,000 m.